ANALISIS FINANSIAL USAHA PENGOLAHAN IKAN ASIN KENDIA (Thynnichthys vaillanti) DI KECAMATAN TERING KABUPATEN KUTAI BARAT - Permatasari, Rina; Helminuddin; Haqiqiansyah, Gusti (2339-1324, 2024)
The purpose of this study is to find out what factors are faced by the kendia salted fish processing business and to find out financially the feasibility of the kendia salted fish processing business with analytical tools such as Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B⁄C Ratio), and Payback period (PP). The type of research data used quantitative data and primary data was obtained by interviewing using a questionnaire. The results showed that with an NPV value of Rp. 94,169,118, IRR of 320%, Net B/C Ratio of 11.75, and Payback Period of 0.43 years 5.1 months 153 days. The results of the financial analysis show that the kendia salted fish processing business is profitable and feasible.